Bologna 3D: la pianificazione partecipata del Piano Strutturale Comunale - Deiana, Andrea; Minghetti, Andrea; Lorenzini, Luca; Africani, Paola (GEOmedia, 2008)
Bologna 3D: the Municipal Structural Plan partecipated planning The Bologna Municipality used 3D GIS solutions by Skyline for opening to citizens the decision process which leaded to its new urban plan (PSC): 3D prospective is enhancing understanding of territory strategical planning, even to nontechnical and common people. A Skyline 3D terrain, produced in TerraBuilder environment from 10 meters DTM and from 50 centimeters per pixel colour imagery, is served online by TerraGate streaming server as basis layer for the delivering of interactive 3D GIS applications made using TerraExplorer Pro's authoring environment, integrating all the significant GIS layers and various informations into many 3D projects, now also available online by installing the free plugin TerraExplorer Viewer.